The Meaning of Emerging Adulthood for the Students at the Public University - Bengi Sullu (Culture & Psychology, 2026)
This study offers a narrative exploration of Arnett’s theory of emerging adulthood. Using narrative inquiry grounded in sociocultural theory of development, it analyzes written paragraphs collected from 50 college students, across two campuses of a public university in four sections of developmental psychology classes. Through values analysis, nine major values are identified as “organizing principles” in making sense of transition to adulthood: Self-sufficiency and freedom; Self-exploration; Family relationships; Macrostructural factors; Financial independence; College; Job experiences; Physical distance/separation from parents/family; Peer relationships. Sub-values reveal the pathways and processes through which each value was expressed and enacted. Values most emphasized by generational status and gender are explored, and attention is paid to the “relational moves” among values expressed by students to unpack the harmony and tension across value expressions. Young people navigate the tensions between familial and societal expectations and their own individual aspirations and endeavors at the nexus of gender, generational status, and unique personal, familial and social circumstances. This study contributes to research focusing on urban college students’ experiences of emerging adulthood and reveals the ways in which individual and social identities, desires and responsibilities are intricately intertwined.